Yard as Environmental Sustainability and Food Security Aisyiyah Durungbedug Branch Leaders in Supporting the SDGs - M Abror; A. Miftakhurrohmat; Andriani Eko Prihatiningrum; Putri Karina Rachmadani; Abdullah Fahmi Rabbani; Canda Kharisma Septabrina; Izza Anshori (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2025)
The utilization of home yards is often suboptimal, despite their great potential in enhancing household food security and environmental sustainability. In collaboration with the ‘Aisyiyah Durungbedug Branch, this program was designed to empower women through community-based management of productive and eco-friendly yards. The activities consisted of preparation, training, mentoring, and evaluation stages. The results demonstrated significant improvements in yard utilization for food and medicinal plants, reduced dependency on chemical fertilizers, and strengthened household food self-sufficiency. Beyond ecological benefits, the program highlighted women’s strategic roles in sustainable development. This initiative addresses the gap of sporadic yard utilization by offering an integrated empowerment model that supports the SDGs, particularly food security, gender equality, and environmental management.